2012
DOI: 10.1128/jb.06490-11
|View full text |Cite
|
Sign up to set email alerts
|

Integration of σ B Activity into the Decision-Making Process of Sporulation Initiation in Bacillus subtilis

Abstract: Spo0AϳP is the master regulator of sporulation in Bacillus subtilis. Activity of Spo0A is regulated by a phosphorelay integrating multiple positive and negative signals by the action of kinases and phosphatases. The phosphatase Spo0E specifically inactivates the response regulator Spo0AϳP by dephosphorylation. We identified a B -type promoter adjacent to spo0E that is activated by the general stress response sigma factor B and is responsible for spo0E induction in vivo. Ectopic expression of B and subsequent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
45
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 64 publications
(72 reference statements)
7
45
0
Order By: Relevance
“…Our finding that mutations in rsbU cause sporulation to be temperature sensitive is consistent with interaction between the stress-responsive and sporulation regulatory pathways and supports a model in which activation of SigB interferes with sporulation (15,16).…”
supporting
confidence: 70%
See 1 more Smart Citation
“…Our finding that mutations in rsbU cause sporulation to be temperature sensitive is consistent with interaction between the stress-responsive and sporulation regulatory pathways and supports a model in which activation of SigB interferes with sporulation (15,16).…”
supporting
confidence: 70%
“…It has long been known that addition of ethanol within a 45-min time period around T 1 of sporulation inhibits spore formation (27), presumably through stimulation of the SigB-dependent stress response. More recently, Reder et al (15,16) reported that the spo0E coding sequence is preceded by a perfect SigB promoter sequence and that ectopic expression of SigB interferes with the onset of sporulation. In a construct in which SigB is expressed from a xyloseinducible promoter, addition of xylose leads to overexpression of spo0E.…”
Section: Discussionmentioning
confidence: 99%
“…and B of endosporulators, which are both involved in the stress response (70). Importantly, B of B. subtilis is not required for sporulation, although B -inducing signals can influence activation of Spo0A (71).…”
Section: Resultsmentioning
confidence: 99%
“…A gene encoding a homolog for the sporulation sigma factor SigK of bacilli is present in the genome of C. botulinum ATCC 3502 (open reading frame [ORF] CBO2541) (11) and was recently shown to be essential in early stage sporulation in C. botulinum (12) and in Clostridium perfringens (13,14) and putatively in transcriptional activation of the sporulation master switch Spo0A of C. botulinum (12). In B. subtilis, recent findings suggest an interesting interconnection between the decision to sporulate and adaptation to stress as nongrowing "vegetative dormant" cells (15,16). These observations propose a role for the stress sigma factor SigB in regulating the activity of Spo0A of B. subtilis.…”
mentioning
confidence: 99%
“…These observations propose a role for the stress sigma factor SigB in regulating the activity of Spo0A of B. subtilis. The lack of sigB in the C. botulinum ATCC 3502 genome suggests that the network for decision making between sporulation initiation and stress adaptation of this organism is regulated differently from the one proposed for B. subtilis (15,16). We thus sought to investigate the behavior and role of the alternative sigma factor SigK in response to stress in C. botulinum ATCC 3502.…”
mentioning
confidence: 99%